Clinical trials for symptoms in patients receiving dialysis - Collister, David (My University, 2021)
Symptoms in patients receiving dialysis are common and associated with impaired quality of life. Symptoms are a top research priority because effective therapies are lacking and even with appropriate diagnosis and treatment, residual symptoms often persist. Clinical trials in the setting of kidney disease are challenging to conduct and as a result, nephrology lags behind other specialties regarding the degree to which clinical trials inform the care of patients with kidney disease, including those receiving dialysis. The studies in this thesis inform the design of randomized controlled trials with regards to run-in periods and the treatment of symptoms in patients with kidney disease. Chapter 2 describes a meta-epidemiologic study of the frequency, setting and purposes of run-in periods in parallel randomized controlled trials of self-administered medications for chronic diseases in adults. Chapter 3 is a study within a trial of an international randomized controlled trial that compares spironolactone to placebo for the prevention of cardiovascular morbidity and mortality in dialysis. It compares the ability of a 3-week study visit in addition to a 7-week study visit during an active-run-in period to identify and exclude participants with non-adherence. Chapter 4 is a protocol for a randomized placebo controlled crossover trial of low fixed dose pharmacologic therapy for restless legs syndrome in hemodialysis that includes a placebo run-in period for adherence and tolerability. Chapter 5 is a survey of Canadian nephrologists regarding the use of cannabinoids for symptom management in patients with kidney disease and support for their use in clinical trials.
Keywords: Symptoms; Dialysis; Run-in period; Clinical trial; Cannabinoids